Strategic Orientation and Absorptive Capacity: The Mediating Role Of Functional Conflict - Ismail, Md Daud; Samsudin, Zurina; Othman, Mohd Salekhan; Hamid, Roshayati binti Abdul (UI Scholars Hub, 2023)
Research Aims: This study investigates the mediating role of functional conflict in explaining the effect of market orientation on the absorptive capacity of small and medium enterprises (SME) exporters in emerging markets. Design/Methodology/Approach: The data were successfully collected from 124 respondents and tested using structural equation modelling via Smart-PLS. Research Findings: The results support the notion that responsive market orientation and proactive market orientation positively influence absorptive capacity. In addition, functional conflicts serve as a quasi-mediator in the relationship between responsive market orientation and absorptive capacity. Theoretical Contribution/Originality: The export competitiveness of SMEs is the output of intangible assets of external knowledge. The ability to identify the relevant knowledge, disseminate that knowledge within the organisation and transform it into valuable products or services is pertinent. Nevertheless, firms vary in terms of the ability to develop absorptive capacity. Accordingly, previous research investigates the antecedent of absorptive capacity, but very few have looked at the role of market orientation and the conditions that influence the relationship. Managerial Implications in the South East Asian Context: Interaction with foreign importers affects SME knowledge development. Functional conflict requires open dialogues to develop meaningful outputs; as such, SMEs in South East Asia should aim to build good connections with their overseas importers. Research Limitations & Implications: The limitations of this study include the small sample size, the external condition of Covid-19 that was not included in this study and the cross-sectional approach of data collection which did not capture the dynamic nature of the firm’s capability.